In vitro maturation (IVM) of oocytes recovered from ovariectomy specimens in the laboratory: a promising “ex vivo” method of oocyte cryopreservation resulting in the first report of an ongoing pregnancy in Europe - Segers, Ingrid (J Assist Reprod Genet, 2015)
PURPOSE: We present our center’s experience with 34 consecutive cases who underwent in vitro maturation (IVM) of oocytes obtained from ovariectomy specimens and compare our data with updated literature data. METHODS: Feasibility and efficiency of oocyte collection during ovarian tissue processing was assessed by the recovery rate, maturation rate, and embryological development after IVM. RESULTS: On average, 14 immature oocytes were retrieved per patient during ovarian tissue processing in 33/34 patients. The overall maturation rate after IVM was 36 %. The maturation rate correlated with the age of the patient and the duration of IVM. Predominately, oocyte vitrification was performed. Eight couples preferred embryo cryopreservation. Here, a 65 % fertilization rate was obtained and at least one good-quality day 3 embryo was cryopreserved in 7/8 couples. The retrieval of oocytes ex vivo resulted in mature oocytes or embryos available for vitrification in 79 % of patients. One patient with ovarian insufficiency following therapeutic embolization of the left uterine and the right ovarian artery because of an arteriovenous malformation had an embryo transfer of one good-quality warmed embryo generated after IVM ex vivo, which resulted in an ongoing clinical pregnancy. CONCLUSIONS: IVM of oocytes obtained ex vivo during the processing of ovarian cortex prior to cryopreservation is a procedure with emerging promise for patients at risk for fertility loss, as illustrated by the reported pregnancy. However, more data are needed in order to estimate the overall success rate and safety of this novel approach.